Impact of liquidity coverage ratio on performance of select Indian banks - Anureet Virk Sidhu; Shailesh Rastogi; Rajani Gupte; Venkata Mrudula Bhimavarapu (Journal of Risk and Financial Management, 2022)
The post-crisis liquidity framework improves banking stability by imposing stricter liquidity requirements. However, consistent bank performance continues to be an essential factor in achieving this goal. This study examines the impact of the liquidity coverage ratio (LCR) on the profitability and non-performing assets (NPAs) of Indian banks using annual data from 2010 to 2019. By applying the dynamic panel data regression technique, we found that compliance with the minimum level of the LCR reduces the net interest margins (NIMs) of banks due to a narrower interest spread, thereby impacting banks profitability. Moreover, the NPAs of the banks tend to grow with an increase in LCR. The study's findings have far-reaching implications for policymakers. Indian policymakers/regulators need to understand the strategies used by banks to meet liquidity standards and, if necessary, revisit the policy framework to achieve better compliance results. The study's framework establishes a foundation that can be used for conducting similar research in other complex geographies such as India.
Keywords: 650; dynamic panel data analysis; LCR; liquidity; NIMs; NPAs; performance